Validation Of Instrument to Measure Gen-Z Pre-Service Teacher Chemistry Virtual Lab Acceptance and Use - Jumriani, Jumriani; Hilman Qudratuddarsi; Nur Rahmah; Dyah Puspitasari Ningthias; Nor Indriyanti (Chemistry Education Practice, 2025)
This study aims to validate the instrument to measure Gen-Z Pre-service Science Teacher Virtual Lab Acceptance and Use using Rasch model. This study is quantitative survey design with 83 participants from science education major in a new public university in Sulawesi. Instrument of the study is adopted which developed based on the Unified Theory of Acceptance and Use of Technology 2 and the Theory of Planned Behavior. Students are requested to fill up the questionnaire after experimenting basic chemistry courses using pHET virtual laboratory. The instrument has satisfactory reliability (person reliability 0.95, item reliability 0.78 and Cronbach alpha 0.98), separation (person separation 4.32 and item separation 1.68). All item are accepted based on the suitability of item fit statistics by referring to mean square, Z tolerated standard, and point measure correlation. Based on its unidimensionality, the instrument can explained 57.7% variance from item variance 22.7% and person variance 30%. Based on the findings that the instrument is valid and reliable to measure science teacher virtual lab acceptance and use. The findings suggest that validated instruments for measuring virtual lab acceptance can guide educators and policymakers in effectively integrating technology into science teacher training programs, ultimately enhancing educational practices and outcomes.